Failure mechanism of (La,Sr)MnO3 oxygen electrodes of solid oxide electrolysis cells - Chen, Kongfa; Jiang, San Ping (Pergamon-Elsevier Science Ltd, 2011)
The delamination behavior of La0.8Sr0.2MnO3 (LSM) oxygen electrode of solid oxide electrolysis cell (SOEC) is studied in detail under anodic current passage of 500 mA cm2 and 800C. The delamination or failure of LSM oxygen electrode is observed after the current passage treatment for 48 h, and is accompanied by the significant increase in the electrode polarization and ohmic resistances. Thedelaminated electrode and electrolyte interface is characterized by the formation of nanoparticles within LSM contact rings on the electrolyte surface. SEM analysis of the interface at different stages of the polarization indicates that the formation of these nanoparticles is caused by the localized disintegration of the LSM grains at the electrode/electrolyte interface. The formation of nanoparticles is most likely due to the migration or incorporation of oxygen ions from the YSZ electrolyte into the LSM grain, leading to the shrinkage of LSM lattice. The shrinkage of the LSM lattice will create local tensile strains, resulting in themicrocrackandsubsequent formationof nanoparticleswithinLSMparticles atthe electrode/electrolyte interface. The formation of nanoparticle clusters weakens the anode/electrolyte interface, eventually leading to the delamination and failure of the LSM oxygen electrode under high internal partial pressure of oxygen at the interface.